2006
DOI: 10.1103/physreva.73.021401
|View full text |Cite
|
Sign up to set email alerts
|

Generation of microscale current loops, atom rings, and cubic clusters using twisted optical molasses

Abstract: We propose a scheme for a viable and highly flexible all-optical atomic cooling and trapping using twisted light. In particular, we explain how one-dimensional twisted optical molasses should lead to a microscale atomic ring or a picoampere ionic current. Two-dimensional and three-dimensional molasses lead, respectively, to the creation of atom or ion loops and discrete atom clusters positioned at the eight corners of a microcube. These features at the microscale should find applications in physics and in quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…[9] Based on the optical torque that was first predicted [10,11] for two-level atoms, some more recent theory work has shown that microscale ion current loops, atomic rings and cubic clusters can be generated using an LG beam-induced optical molasses configuration. [12] In the broader context of atomic motions produced by LaguerreGaussian light, it is interesting to reflect on the pioneering work of Andersen et al, [13] which established a new protocol for an almost frictionless circulation of ultracold sodium atoms, also using counter-propagating LG beams to create the torque. More recently two of us (VEL, MB) have shown that it is possible for a persistent current flow to be produced in an atomic gas Bose-Einstein condensate, using counterpropagating LG beams to create a toroidal trap.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Based on the optical torque that was first predicted [10,11] for two-level atoms, some more recent theory work has shown that microscale ion current loops, atomic rings and cubic clusters can be generated using an LG beam-induced optical molasses configuration. [12] In the broader context of atomic motions produced by LaguerreGaussian light, it is interesting to reflect on the pioneering work of Andersen et al, [13] which established a new protocol for an almost frictionless circulation of ultracold sodium atoms, also using counter-propagating LG beams to create the torque. More recently two of us (VEL, MB) have shown that it is possible for a persistent current flow to be produced in an atomic gas Bose-Einstein condensate, using counterpropagating LG beams to create a toroidal trap.…”
Section: Discussionmentioning
confidence: 99%
“…(6) and (4) are in cylindrical polar coordinates, with the beams propagation along the z axis, and we need to obtain expressions for a second counterpropagating beam traveling along the negative z axis. This is done by a simple coordinate transformation so that both beams are expressed relative to the same coordinate system [7,8].…”
Section: Doppler Mechanism With Lg Lightmentioning
confidence: 99%
“…In a series of recent experiments involving twisted light, Anderson et al [1] demonstrated that sodium atoms in a Bose-Einstein condensate can be trapped in the annular region of a Laguerre-Gaussian (LG) doughnut beam and be made to rotate by the light-induced torque [2][3][4][5][6][7][8][9], thus creating a longlived persistent current. A recent analysis of another scenario suggests that counterpropagating beams create a light-induced torque which would be more effective in the formation of a persistent current [10].…”
Section: Introductionmentioning
confidence: 99%
“…The prototypical example is the set of modes known as Laguerre-Gaussian (LG) laser beams, which can now be routinely created in the laboratory. The interaction of matter in the form of atoms, ions, molecules, or small particles of bulk matter with LG light has been considered both theoretically and experimentally, leading to translational and rotational effects, as well as to trapping in various situations [6][7][8][9][10][11][12]. More recently, the interference of LG beams has been shown to give rise to rotating patterns, called optical Ferris wheels [13], and the beams have been shown to give rise to evanescent surface optical vortices as interface modes which possess orbital angular momentum [14].…”
Section: Introductionmentioning
confidence: 99%